PENGALAMAN KERJA SEBAGAI PEMODERASI PENGARUH DUE PROFESSIONAL CARE PADA KUALITAS AUDIT - Annisa, Natasha Rizky; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
This study was conducted to determine the effect of due professional care on audit quality and auditor experience influence in the relationship between experience with audit quality. This research was conducted in the Public Accounting Firm (KAP) of Bali which amounted to a total of seven KAP all auditors by 80 auditors. In this study using purposive sampling technique. Data analysis technique used is the technique of regression moderation. The response in this study of 54 questionnaires, with the amount used as many as 33 questionnaires. Based on the results of simple regression analysis found that due professional care positive effect on audit quality. This shows that the higher the professional due care it will produce a high quality audits. Moderation of the regression results found that work experience which is able to moderate the impact that the weakened due professional care in audit quality.
Keywords: Due Professional Care, Work Experience, Quality Audit